ANALISIS PENGARUH KETERLIBATAN KERJA DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN (Studi Pada PT. Njonja Meneer Semarang) - Simanjuntak, Naomei; Rahardja, Edy (Diponegoro Journal of Management, 2013)
High employee turnover rate may result the organization not effective and eficient. Organization must minimalism turnover intention so organization will not miss the experience employee and no expense useless. This research aims to analyze the influence of job involvement and job satisfaction on turnover intention of employees. This research was conducted in PT. Njonja Meneer Semarang to the number of samples set 101 respondents. The method used is Purposive Sampling and method data anlysis is used multiple linear regression analysis, using SPSS program.The results ofÂ  testing hypotesis, shows that job involvement has negative and significant influence on turnover intention of emloyees and Job satisfaction has negative and significant influence one turnover intention of employees. The results of determination are 0,482 indicates that the capability of independent variabels (job involvement and job satisfaction) in explaining the dependent variable (turnover intention) is 48,2%.